Comparative Rates of Androgen Production and Metabolism in Caucasian and Chinese Subjects - Santner, S. J. (The journal of clinical endocrinology and metabolism, 1998)
Clinically apparent prostate cancer occurs more commonly among Caucasians living in Western countries than in Chinese in the Far East. Prior studies demonstrated diminished facial and body hair and lower levels of plasma 3 alpha-androstanediol glucuronide and androsterone glucuronide in Chinese than in Caucasian men. Based upon these findings, investigators postulated that Chinese men could have diminished 5 alpha-reductase activity with a resultant decrease in prostate tissue dihydrotestosterone levels and clinically apparent prostate cancer. An alternative hypothesis suggests that decreased 3 alpha-androstanediol glucuronide and androsterone glucuronide levels might reflect reduced production of androgenic ketosteroid precursors as a result of genetic or environmental factors. The present study examined 5 alpha-reductase activity, androgenic ketosteroid precursors, and the influence of genetic and environmental/dietary factors in groups of Chinese and Caucasian men. We found no significant differences in the ratios of 5 beta-:5 alpha-reduced urinary steroids (a marker of 5 alpha-reductase activity) between Chinese subjects living in Beijing, China, and Caucasians living in Pennsylvania. To enhance the sensitivity of detection, we used an isotopic kinetic method to directly measure 5 alpha-reductase activity and found no difference in testosterone to dihydrotestosterone conversion ratios between groups. Then, addressing the alternative hypothesis, we found that the Caucasian subjects excreted significantly higher levels of individual and total androgenic ketosteroids than did their Chinese counterparts. To distinguish genetic from environmental/dietary factors as a cause of these differences, we compared Chinese men living in Pennsylvania and a similar group living in Beijing, China. We detected a reduction in testosterone production rates and total plasma testosterone and sex hormone-binding levels, but not in testosterone MCRs in Beijing Chinese as a opposed to those living in Pennsylvania. Comparing Pennsylvania Chinese with their Caucasian counterparts, we detected no significant differences in total testosterone, free and weakly bound testosterone, sex hormone-binding globulin levels, and testosterone production rates. Taken together, these studies suggest that environmental/dietary, but not genetic, factors influence androgen production and explain the differences between Caucasian and Chinese men.